THE HUNGARIAN GOVERNMENTAL DEFENCE AND MILITARY DEVELOPMENT PROGRAM „ZRÍNYI 2026” AS A RESPONSE TO THE NEW THREATS IN THE REGION - BALOGH Olivér (2018)
The purpose of the article is to illustrate the Hungarian Governmental Defence and Military Development Program „Zrínyi 2026”, enacted in 2016, and its role in national and regional European security. The author focuses not only on the military technical changes, that include addition of the new equipment, but also discusses the organizational and structural changes promoted by the program. Presented analysis also elaborates on the defence budget and its forecast up to 2024, with discussion on major implications. Thorough this emphasis structure of the Armed Forces of Hungary, as of January 2019, is presented, in view of changes caused by modern threats in the region.